Investment Dynamics in the Indonesian Defense Industry: A Literature Study Analysis - Susan Cintia Damanik; Herlina Tarigan; Ari Pitoyo Sumarno; Hikmat Zakky Almubaroq (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
In the realm of national security and sovereignty, Indonesia’s defense industry serves as a cornerstone, with its investment dynamics playing a significant role. This study offers a detailed analysis of these dynamics over the past decade, employing a comprehensive literature review methodology. It synthesizes information from a range of primary and secondary sources to unveil complex investment patterns, challenges faced by the industry, and the potential for growth and advancement. Scrutinizing the multifaceted factors that drive investment decisions, this study uncovers how geopolitical, economic, and security considerations, both globally and regionally, have influenced the industry. A notable finding is the strong correlation between an uptick in investments and advancements in technological innovation and industry autonomy. Despite positive developments, the study highlights ongoing challenges like stringent regulatory frameworks, a need for greater transparency, and the urgency of improving sector efficiency. A shift towards a more independent and technologically advanced defense industry in Indonesia is discernible, spurred by strategic investments. The study also sheds light on the pivotal role of foreign direct investment (FDI) in enhancing technological capabilities and catalyzing the growth of local industries via collaborative ventures. In terms of policy, the paper advocates for reformative strategies that reconcile national interests with the necessity of global economic integration. It suggests a suite of policy recommendations designed to promote a conducive investment environment, encouraging private sector involvement and international cooperation in alignment with Indonesia’s defense objectives. The conclusion asserts the feasibility of a sustainable and burgeoning defense industry through strategic and informed investment approaches. It calls for continued research and open dialogue among policymakers, industry players, and academics to effectively navigate the investment landscape of Indonesia’s defense sector, ensuring its alignment with broader economic goals.